FRI0455 High intensity aerobic exercise in ankylosing spondylitis reduces arterial stiffness: results from a randomized controlled trial. (23rd January 2014) - Berg, I. J.; Semb, A. G.; Halvorsen, S.; Fongen, C.; Dagfinrud, H.; Kvien, T. K.; Provan, S. A.
Abstract : Background: Patients with ankylosing spondylitis (AS) are at increased risk of cardiovascular disease (CVD). However, we do not know etiological mechanism or how to reduce risk. Exercise is known to reduce cardiovascular (CV) risk in the general population. Objectives: A proof of concept investigation to test whether high intensity aerobic exercise reduces CV risk factors and risk markers in AS patients. Methods: A randomized controlled pilot study was carried out at Diakonhjemmet Hospital, Norway in 2011-2012. Inclusion criterion was active AS with BASDAI>3.5. The patients were allocated to either the exercise group (EG) or a control group (CG). The exercise program consisted of aerobic high intensity training 40 minutes 3 days a week and muscular strength training 20 minutes twice a week. The training was supervised twice a week. The intervention lasted for 3 months. The control group received care as usual. Participants were assessed at baseline and at 3 months for CV risk factors (blood pressure, lipids, BMI) and arterial stiffness (using applanation tonometry, calculating augmentation Index (AIx) and pulse wave velocity (PWV)). Statistical analyses were performed using SPSS 20, using Mann-Whitney U test to compare median change (from baseline to 3 months) of the parameters between EG and CG. Analyses were performed pr protocol. Results: 28 AS patients were recruited to the study. Two patients did not perform testing after 3 months, 1 in EG and 1 in CG, and two additional patients did not adhere to the exercise program. Thus 24 patients fulfilled the study, 10 in the EG and 14 in the CG. There were some differences in demographics (EG vs. CG): age, years (median (min-max)) 43 (30-67) vs. 50 (26-68), male gender: 20% vs. 71%. After the study period, arterial stiffness was reduced in the EG compared CG, both significant for AIx (%) median (min-max) -3.3 (-24.5-2.5) vs. 1.7 (-13.5-10.3), p=0.04 and for PWV (m/s) median (min-max) -0.4 (-1.9-0.1) vs. -0.1 (-1.5-0.1), p=0.05 (figure ). There were no significant group differences in change of traditional CV risk factors (systolic blood pressure, diastolic blood pressure, total cholesterol, LDL, HDL, triglycerides, BMI). No adverse events were observed. Image/graph: Conclusions: This proof of concept study showed that intervention with high intensity aerobic exercise reduced arterial stiffness after 3 months compared to controls. The results of this small study need replication in larger RCT with longer follow-up. Disclosure of Interest: None Declared